Evaluation of viral co‐infections in hospitalized and non‐hospitalized children with respiratory infections using microarrays. (1st October 2012) - Kouni, S.; Karakitsos, P.; Chranioti, A.; Theodoridou, M.; Chrousos, G.; Michos, A.
Abstract: The impact of viral co‐infections and recently discovered viruses on the epidemiology of respiratory infections in children is still unclear. To simultaneously detect viruses that are involved in the aetiology of respiratory infections, we used a DNA/RNA microarray assay that identifies 17 different viruses or viral subtypes. Rhinopharyngeal washes were taken from 611 children (aged 1 month to 14 years) who presented in the emergency department with respiratory infections from June 2010 to June 2011 and were treated as outpatients (299, 48.9%) or hospitalized (312, 51.1%). Lower respiratory tract infection was diagnosed more often in hospitalized children (68% versus 36%, p 0.001). Of 397 children in which microarrays detected viral infection (70.1%), a single virus was found in 228 (57.4%) and two or more viruses in 169 (42.5%). The most prevalent viruses among children with positive samples were respiratory syncytial virus (RSV) in 225 (56.6%), parainfluenza virus (PIV) in 118 (29.7%), rhinovirus (RV) in 73 (18.4%), followed by influenza in 56 (14.1%), adenoviruses in 31 (7.8%), bocavirus in 25 (6.3%), human metapneumovirus in 15 (3.7%) and enteroviruses in 12 (3%). Most common viral co‐infections were RSVA–RSVB in 46 children (27.2%), RSV–Influenza in 20 (11.8%), RSV–RV in 18 (10.6%) and PIV–RV in 13 (7.7%). Multiple logistic regression analysis revealed that viral co‐infections were associated with increased probability for hospitalization (OR 1.52, 95% CI 1.01–2.29, p 0.04), and previous pneumococcal vaccination was associated with decreased probability for hospitalization (OR 0.52, 95% CI 0.33–0.81, p 0.004). We conclude that viral co‐infections are involved in a significant proportion of children with an acute respiratory infection and may increase the severity of clinical presentation and the risk for hospitalization.